Interactive text: from the act of reading to the interactivity of authorship - hamrit, rima (El Omda in Linguistics and Discourse Analysis, 2022)
The interactive literary experience has increased from the reader's role and granted him the status of a producer through his contribution to rewriting the text. As he was not left content with following up, but writing and moving in the text according to his choices and capabilities that embodied the substitution from the power of reading to the announcement of the act of production (authoring), because this type of text is a new carrier of the element of open imagination to informational and virtual procedures that made each reading constitute a new substitution For a total work. Here, the question can be posed to what extent can the continuity of the reproduction of texts be ensured through interactive fisheries through substitution and intersection between the author's tasks as a true producer of the text and the virtual reader with his conditional active presence